Prevalence of Child Physical Abuse among School Children in Mosul City\North of Iraq (Medico Legal Update, 2021)
Background and Aims: Physical abuse is the most critical problem in Mosul city children and the extent ofphysical abuse is currently unknown. Aim of this study to determine the prevalence of physical abuse amongsample of Mosul schoolchildren, aged 12–18 years.Material and Method: A cross-sectional study was carried out from 1st, December 2018 to 4th March 2019.The settings chosen by multicultural sampling with a systematic sampling technique of 800 child (396 maleand 404 female) using a self-reported questionnaire.Result: A total of 800 intermediate school children, age group 14-15 years represent 43.6%, male to femaleratio 1:1, 36.1% of these had experienced physical abuse and 32.6% abused by mothers. The relationshipbetween the parent educations and father’s job shows high significant rate 0.000, 0.004.Conclusion: physical abuse Mosul city had high prevalent in comparison with others. Psychological andphysical problems of children were the main predictors.